How is the Ramkye Bhyea` or Hela Tali' Tradition Ceremony Procession - Bety D.S Hetharion (Peneliti.net, 2021)
The aims es of implementing the ramkye bhyea tradition are: 1) to treat the marine environment from damaging marine biota. 2) the number of fish is more for the needs of the community. (3) Improving the welfare of families in Serili together because the fish caught can be eaten and stored for a long time. 4) develop brotherly relations between communities. 4). Can be sold to neighboring village communities, 4). Build a spirit of militancy to face the harsh and difficult natural environment. This research method uses aapproach historical by trying to understand the history and development of thetradition Ramkye Bhyea in Serili Village, Marsela District, Southwest Maluku Regency in order to obtain accurate data. The results showed that Ramkye byea is a tradition of catching fish in the sea using young coconut leaves tied to rattan or rope. Ramke Bhyea is referred to as a tradition because since 1946 when ramkye bhyea was introduced with the term pulling rope, it has been maintained and carried out every year in October.